Pembangunan Jabar Selatan : potensi, permasalahan dan prospeknya (sebuah rekaman pers) - Jawa barat (Indonesia) Badan Perencanaan (Bandung : BAPPEDA, Jawa Barat, 1997)
Economic conditions and tourist objects, southern part of West Java, Indonesia.
Keywords: Tourism -- Indonesia -- Jawa Barat; Jawa Barat (Indonesia) -- Economic policy; Jawa Barat (Indonesia) -- Economic conditions